The Vital Dynamism of the Voice in Diderot - Hélène Cussac (Etudes Epistémè)
Conscious of the difficulty of expressing sound in a culture still under the influence of a form of rationalism that privileges the sense of sight over the sense of hearing, Diderot never stopped inscribing and exploring the voice in his philosophical work and at times in his novels. This article looks at the way in which the materialist writer attempts to rehabilitate the human voice as a sign of vitality, working from the internal tension between the simultaneous presence of both negative and positive sounds, between annoyance and attraction to sounds. The article shows that Diderot experiments with the sensibility of matter in his characters, at times even describing the energy and the excess of a vibrant voice; but he also speaks about the strength of the human voice when passionate – a voice which might finally lose its perfectibility, but by the same token extracts itself from the silence imposed by the religious and political context. For Diderot, to represent the voice is thus to act both as an esthete and as an anthropologist, but it also has a political dimension.